Active efflux of dasatinib from the brain limits efficacy against murine glioblastoma: broad implications for the clinical use of molecularly-targeted agents - Agarwal, Sagar (2012)
The importance of the blood-brain barrier in preventing effective pharmacotherapy of glioblastoma has been controversial. The controversy stems from the fact that vascular endothelial cell tight junctions are disrupted in the tumor, allowing some systemic drug delivery. P-glycoprotein (Pgp) and breast cancer resistance protein (BCRP) efflux drugs from brain capillary endothelial cells into the blood. We tested the hypothesis that although the tight junctions are “leaky” in the core of glioblastomas, active efflux limits drug delivery to tumor-infiltrated normal brain and consequently, treatment efficacy. Malignant gliomas were induced by oncogene transfer into wild-type (WT) mice or mice deficient for Pgp and BCRP (KO). Glioma-bearing mice were orally dosed with dasatinib, a kinase inhibitor and dual BCRP/PgP substrate that is being tested in clinical trials. KO mice treated with dasatinib survived over twice as long as WT mice. Microdissection of the tumor core, invasive rim, and normal brain revealed 2-3 fold enhancement in dasatinib brain concentrations in KO mice relative to WT. Analysis of signaling demonstrated that poor drug delivery correlated with the lack of inhibition of a dasatinib target, especially in normal brain. A majority of human glioma xenograft lines tested expressed BCRP or PgP and were sensitized to dasatinib by a dual BCRP/Pgp inhibitor, illustrating a second barrier to drug delivery intrinsic to the tumor itself. These data demonstrate that active efflux is a relevant obstacle to treating glioblastoma and provide a plausible mechanistic basis for the clinical failure of numerous drugs that are BCRP/Pgp substrates.